2001
DOI: 10.1097/00041433-200104000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of sitosterolemia

Abstract: The molecular mechanisms regulating the amount of dietary cholesterol retained by the body, as well as the body's ability to exclude other dietary sterols selectively, are poorly understood. An average Western diet will contain approximately 250-500 mg of dietary cholesterol and approximately 200-400 mg of non-cholesterol sterols, of which plant sterols are the major constituents. Approximately 50-60% of dietary cholesterol is absorbed and retained by the normal human body, but less than 1% of the non-choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 31 publications
6
114
0
2
Order By: Relevance
“…Other studies reported the same observations [42], and mutations in two tandem ABC genes, ABCG5 and ABCG8, encoding sterolin-1 and 2, respectively, are now known to be mutant in sitosterolemia. Heterozygous individuals do not develop the disease, but present raised plasma phytosterol concentrations [64][65][66].…”
Section: Phytosterolemia or Sitosterolemia: Abcg5/g8 Mutationssupporting
confidence: 54%
“…Other studies reported the same observations [42], and mutations in two tandem ABC genes, ABCG5 and ABCG8, encoding sterolin-1 and 2, respectively, are now known to be mutant in sitosterolemia. Heterozygous individuals do not develop the disease, but present raised plasma phytosterol concentrations [64][65][66].…”
Section: Phytosterolemia or Sitosterolemia: Abcg5/g8 Mutationssupporting
confidence: 54%
“…Patients with this disease develop xanthomas and premature atherosclerosis [24,25]. Affected individuals show high concentrations of plant sterols in plasma due to the fact that, in contrast to healthy subjects, they efficiently absorb these sterols from the intestine and are unable to excrete them into the bile [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…The reason suggested by Mi-Hye Lee et al is that the net effect of the complete loss of function of either 'sterolin', two genes transcribed in opposite directions and encoding ABCG5 and ABCG8, results in increased cholesterol and sitosterol absorp- tion, and decreased sitosterol and cholesterol excretion into bile 26) . However, despite having normal plasma cholesterol levels, sitosterolemic patients often develop premature coronary heart disease (CHD), which suggests that high circulating levels of plant sterols per se might be atherogenic, even in non-sitosterolemic subjects.…”
Section: Plant Sterols and Cardiovascular Diseasesmentioning
confidence: 99%